Labour immigration and São Paulo's textile sector: notes of bolivian presence in the garment factories - Coutinho, Beatriz Isola (Universidade Estadual de Campinas, UNICAMP, Unidade da Faculdade de Ciências Aplicadas de Limeira-SP, vinculada ao Laboratório de Estudos do Setor Público, LESP, 2012)
The growth of the hispanic presence in São Paulo city, mostly bolivian immigrants in the last decade, is commonly related with the garment production in small factories. It is a complex phenomenon, whose discussion is increasingly in the academia, institutional environment and media. Placed in the context of globalization, is permeated with illegality and inherent dynamics migration events. In this article, we present some features through dialogue between concepts and immigration study methodologies, articulating them with specific bibliography about Andean workforce in São Paulo’s textile sector.